Malibongwe - South African women united
Bord onregelmatig formaat. Logo van de Malibongwe conference on the women's struggle in South Africa in Amsterdam, januari 1990, georganiseerd door de Anti-Apartheids Beweging Nederland (AABN), Amsterdam i.s.m. de ANC Women's Section.